Penerapan Model Pembelajaran Kooperatif dengan Media Audio Visual Berbasis Teknologi Untuk Meningkatkan Aktivitas dan Kemampuan Menyimak Mahasiswa - Resnani, Resnani (Jurnal PGSD, 2019)
This research aims to increase the activity and listening skill of students through a cooperative learning model of technology-based audio visual media at the course of language basic skills. The subjects were the students of PGSD in III B class academic year 2019/2020 which amounted to 40 students. The research instruments were observation sheets and test sheets of the listening skill. The observation data was analyzed by using the average score and the data of the listening capabilities analyzed by using of the average value and percentage. The results showed that (1) the implementation of cooperative learning models with technology-based visual audio media at the course of the language basic skills can increase the learning activity,  (2) The application of cooperative learning model with technology-based audio visual media in the course of basic language skills can enhance the ability to listen of students who are infused with the ability to listen to the students each cycle increases. The average scor of the students ' listening skills at the first cycle is 78.05 with a detailed guidance of a kilacical study is 77.5% increased in the second cycle the average value of the student's listening capability is 83.25 with the classical guidance of the study is 92.5%. It is thus concluded that the application of cooperative learning models with technology-based audio visuals can increase the activity and listening skill  of IIIB students at the language Basic skills Lecture at the PGSD University of Bengkulu.